Prediksi Variabilitas Nilai Tukar Rupiah Indonesia Terhadap Dollar Amerika Serikat Berbasis Sistem Inferensi Fuzzy Jaringan Saraf Adaptif sebagai Analisis Tingkat Perekonomian - Gernowo, Rahmat; Ernitawati, Yenny (JURNAL SAINS DAN MATEMATIKA, 2013)
The purpose of this paper to predict the variability of exchange rate (Rp/ US $) based Adaptif Neuro-Fuzzy Inference Systems (ANFIS)Â  analysis of the economic level. The data is secondary data obtained from the movement of the exchange rate (Rp / US $) in Bank Indonesia from January 2003 to December 2013 . The software is used among others of ANFIS system. The results obtained with the Neuro-Fuzzy system shows the range of estimates for all data were obtained at 89.51% for treatment with ANFIS. Dollar exchange rate variability index, showed a pattern that tends to stabilize after years in which Indonesia was hit by the financial crisis of 1998.. Â  Keywords: Prediction, dollar exchange rate index, ANFIS.